THE EFFECT OF LEXICAL STRATEGIES AND THE VOCABULARY MASTERY ON THE STUDENTS’ VOCABULARY ACHIEVEMENT - Rosi Heftania; Amrin Saragih; Anni Holila Pulungan (Universitas Negeri Medan, 2018)
The objectives of the study are to describe whether : 1). Students’ vocabulary mastery taught by inferencing strategies (IS) higher than taught by Lexical Processing Strategies (LPSs) in students’ vocabulary achievement.2) Students’ who have high vocabulary mastery is significantly higher than students’ who have low vocabulary mastery in students’ vocabulary achievement. 3) The effect of simultaneously applying both Lexical Strategies and Vocabulary mastery on the students’ vocabulary achievement. An experimental research with factorial design 2x2 was used in this study. There was 80 students from grade X of 2017/2018 academic years of MAN 1 Takengon as sample of this study. The students divided in two groups. Each group consists of 40 students. The first group was treated by using Lexical Inferencing Strategies and the second group was treated by Lexical Processing Strategies. Vocabulary of the two groups was measured by giving questionnaire to classify the students having high and low vocabulary mastery, and achievement test measure by giving multiple choice test to know students’ achievement in vocabulary mastery. The data are analyzed by applying two-way ANOVA at the level significance ɑ = 0.05. The findings of the data shows that. 1) The students’ vocabulary mastery taught by using Lexical Inferencing Strategies was higher than that taught by using Lexical Processing Strategies, with Fobs (19.72) > Ftab (3.25). 2) The Vocabulary Achievement of the students who have high vocabulary mastery was higher than students who have low vocabulary mastery, with Fobs (2691.93) > Ftab (3.25). 3) There was significance interaction between teaching Lexical Strategies and Vocabulary Mastery on the students’ vocabulary achievement, with Fobs (3.27) > Ftable (3.25).